The Effect of Citronella oil Concentration on Physicochemical Properties of Laponite Hydrogel and Antimicrobial Activity Test to Streptococcus aureus ATCC 25923 and Candida albicans ATCC 14053 - Ermawati, Dian Eka; Putriana, Susanti; Susanto, Nindita Claurisa Amaris (Smart Medical Journal, 2024)
Introduction: The Citronella plant produces 78 -85% citral oil. This oil has antimicrobial activity. The oil was developed as an antimicrobial topical and incorporated into laponite hydrogel for optimal use. Laponite hydrogel has a cooling sensation and is compatible with polar and non-polar active substances. This study aims to evaluate the effect of citronella oil concentration on physicochemical properties and examine its antimicrobial activity.Methods: The Citronella plant was distilled using the steam distillation method and analyzed using the GC-MS. The laponite hydrogel was prepared with three concentrations: 6%, 8%, and 10%. Physicochemical properties included pH value, viscosity, stickiness, spreadability, and organoleptics, and the chosen formula was tested for antimicrobial activity. The research data were compared with relevant literature, and ANOVA statistics were analyzed with a confidence level of 95%.Results: Based on the research results, increasing the concentration of citronella oil caused the laponite hydrogel to become increasingly cloudy, viscosity, and sickness but decreased the pH and spreadability. Citronella oil concentration of 8% is the chosen formula that fulfills the best hydrogel preparation with evaluation results of pH value of 7.24 ± 0.064, spreadability of 5.68 ± 0.320 cm, thickness of 1.25 ± 0.012 seconds, and viscosity of 23596.3 ± 227.55 mPa. s. The citronella oil hydrogel has antibacterial and antifungal properties and moderate strong inhibitory.Conclution: As a delivery system for citronella oil, Laponite can be developed as a pharmaceutical preparation to treat mouth ulcers as an alternative synthetic product with good antimicrobial potential.